Reinfection of Nine-Valent Human Papillomavirus Vaccine Types Among HIV-Negative Men Who Have Sex With Men: A Prospective Cohort Study - Liu, Lirong; Zhang, Guozhen; Zhang, Zewen; Wang, Lu; Wang, Duolao; Dai, Jianghong (Frontiers in Public Health, 2022)
Abstract Objectives: Reinfection of human papillomavirus (HPV) among men who have sex with men (MSM) after clearing the infection of HPV has not been well characterized. To understand the reinfection of HPV among human immunodeficiency virus (HIV) negative MSM without HPV vaccine, we analyzed the reinfection of nine-valent HPV vaccine (9v-HPV) types. Methods: Data were acquired from a prospective cohort study among HIV-negative MSM in Urumqi of Xinjiang from April 1, 2016, to July 14, 2020. Participants were recruited through a local non-government organization using a website advertisement. Self-administered questionnaires and self-collected anal swabs were collected at baseline and every 6 months. The incidence rates of reinfection and initial infection were calculated based on the number of events divided by person-months of observation of event risk. 95% confidence intervals (CIs) were calculated based on the Poisson distribution. Results: A total of 515 HIV-negative unvaccinated MSM were included with a mean age of 30.93 years (SD 7.85), and 27.68% were reinfected with any 9v-HPV type after clearance. The reinfection incidence rate of any 9v-HPV was 14.47 per 1000 person-months (95%CI: 11.52- 17.87). HPV52 was the most common type of reinfection, with a reinfection rate of 17.96 per 1,000 person-months (95%CI: 11.58-26.33). Univariate analysis showed that MSM over the age of 30 had a slightly higher risk of reinfection with any 9v-HPV (Hazard Ratio (HR): 1.57; 95%CI: 1.01-2.45), but no significant association was observed in multivariate analysis. Conclusions: Our study found a high rate of anal 9v-HPV reinfections among HIV-negative unvaccinated MSM, suggesting that vaccination in MSM may be crucial to reducing the prevalence of HPV.